A HERMENEUTIC PHENOMENOLOGICAL STUDY TO EXPLORE THE LIVED IN EXPERIENCE OF ADULT TRANSGENDERS IN ACCESSING HEALTH CARE SERVICES FROM PUBLIC INSTITUTIONS IN PUDUCHERRY INDIA - Rafi, Mohammed (LIFE: International Journal of Health and Life-Sciences, 2017)
The researcher conducted a qualitative study among adult transgenders to explore the lived in experience of accessing health care from public institutions in Puducherry, India. The main objectives included to explore the lived in experience of the transgenders, to determine the experience and stigma and to describe the problems and challenges faced by the transgenders in accessing the health care. The researcher adopted hermeneutic phenomenological design. A semi-structured interview method was adopted to get the data among ten adult transgenders from Puducherry who were purposively selected for the study. Each participant was interviewed twice for 45-60 minutes. The collected data were digitally recorded and were transcribed into data. The initial analysis was made by Computer assisted Qualitative data analysis software NVivo9.0 and then was manually analyzed. The result finding included five major themes. The themes include 1.Transgenders: Who am I? 2. Transgenders: A Social Element, 3.Transgenders: The unmet Social Needs, 4.Transgenders and the health care team members: the self -invited relatives 5.Transgenders and the health needs: the unidentified gap. The study findings demonstrate the stigma and discrimination felt by the transgenders in the health institutions and the need for the focus on the transgenders health. The final results of the study shows that the transgenders though the less representation of the population face more health related problems due to inability to access the health care services from the public institutions due to the gap in the health facilities and the needs of the transgenders. The motto “Health for All” though is a target in the recent times, is still a fairy tale for most of the transgenders accessing health in Puducherry and all other states of India.